Policy Analysis on Sending Misbehaving Students to Military Barracks from the Perspective of Development Law and National Defense - Diani Sadiawati; Ivan Nurchalik; Bernard Sindak Pangihutan Lumban Siantar; Exal Sinaga; Hammamtio Hammamtio (Utan Kayu Publishing, 2025)
Recently, populist policies have increasingly been adopted by public officials to enhance their political image, including education-related policies issued by the Governor of West Java, which subsequently sparked criticism from various stakeholders. Therefore, this study aims to examine the policy of sending “problematic” students to military barracks through the lens of development law and a responsive, socially just conception of national defense (bela negara). This research employs a normative juridical method using a scientific approach that includes the statute approach and the conceptual approach. The findings of this study indicate that the policy of sending students to military barracks requires thorough legal examination to ensure that its legal objectives are clear and do not violate human rights. This is particularly important as not all members of society agree with such a policy; the aim of national defense is not the militarization of children but the internalization of Pancasila values and moral discipline. Thus, sending students to military barracks does not automatically align with the concept of national defense when the measures implemented are coercive, discriminatory, and unsupported by psychological and pedagogical educational principles. Furthermore, this policy is inconsistent with the characteristics of responsive development law, which prioritizes the protection of vulnerable groups and emphasizes social justice. A comprehensive evaluation of this policy is therefore necessary, taking into account sociological, legal, and human rights perspectives, as well as educational and rehabilitative approaches.